Monolithic crystal filters using lithium tantalate crystal - I. MATEESCU; G. GACKOWSKA; G. KORONY; C. BORA (Archives of Acoustics)
The characteristics of lithium tantalate crystal filters and the method of their design are described. The experimental results are presented and discussed.